2006
DOI: 10.1258/004947506777978253
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia among adolescent girls in the urban slums of Vellore, south India

Abstract: A community-based, cross-sectional study was conducted to determine the prevalence of anaemia among unmarried, adolescent south Indian girls in an urban slum setting. A total of 100 apparently healthy girls between the ages of 11 and 18 years were recruited. Their socioeconomic, dietary and anthropometric information was collected, and blood haemoglobin (Hb) was estimated. The prevalence of anaemia (Hb < 12 g%) was 29%. Most had mild anaemia; severe anaemia was not seen. Two-thirds of those with anaemia had lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Three fourth of all the anemic students had decreased serum ferritin. Iron deficiency constituted 79% of all anemia, this is similar to the findings of Choudhary A et al (2006) 10 where in also three fourth of all anemic were iron deficient. In the study done in Western Iran by Akramipour R et al (2008) 8 57.3% of anemic girls were iron deficient.…”
Section: Prevalence Of Iron Deficiency Anemiasupporting
confidence: 90%
See 1 more Smart Citation
“…Three fourth of all the anemic students had decreased serum ferritin. Iron deficiency constituted 79% of all anemia, this is similar to the findings of Choudhary A et al (2006) 10 where in also three fourth of all anemic were iron deficient. In the study done in Western Iran by Akramipour R et al (2008) 8 57.3% of anemic girls were iron deficient.…”
Section: Prevalence Of Iron Deficiency Anemiasupporting
confidence: 90%
“…Firm policies should be developed for vitamin and mineral supplementation in adolescents with political commitment. 10 Vellore 29% Bulliyy G et al (2007) 11 Orissa 96.5% Muthayya S et al(2007) 12 Bangalore 15.3% Kapoor G et al(1992) 13 Delhi 50.3% Sidhu S et al(2005) 14 Punjab 70.57% Sen A and Kanani(2006) 15 Gujarat 67% …”
Section: Prevalence Of Iron Deficiency Anemiamentioning
confidence: 99%
“…Anemia has a negative effect on cognitive performance in adolescents [1]. Choudhary, et al [2] reported two-thirds of the anemic adolescents in community were suffering from iron deficiency anemia (IDA). In a study by Patra, et al [3] on severely anemic adolescents admitted in a tertiary care hospital, megaloblastic anemia was most common type of anemia (42.5%) and iron-deficiency accounted for 15% cases [3].…”
mentioning
confidence: 99%
“…In the present study the incidence of adolescent patients hospitalized with a primary diagnosis of severe anemia was found to be 1.90% where as in a similar study by Patra et al [7], have reported the incidence of 3.37%. Though iron deficiency anemia has been reported as most prevalent anemia in adolescent age group in India [5,6], the commonest type of anemia in the present study was megaloblastic anemia (51.28%) followed by iron deficiency anemia (30.77%) and dimorphic anemia (15.38%). One case of aplastic anemia (2.56%) was also found.…”
Section: Discussionmentioning
confidence: 57%
“…Iron deficiency anemia is the most prevalent anemia in adolescent age group in India. Several community studies have reported upto 60% of adolescents having iron deficiency anemia [5,6]. Some community based studies showed that megaloblastic anemia is also common in India.…”
Section: Introductionmentioning
confidence: 99%